Subnational Doing Business in Brazil 2021 : Comparing Business Regulation for Domestic Firms in 27 Brazilian Locations with 190 Other Economies - World Bank Group (World Bank, Washington, DC, 2021)
Subnational Doing Business in Brazil 2021 focuses on business regulations and their enforcement. It goes beyond Rio de Janeiro and São Paulo to benchmark other Brazilian locations across five regulatory areas. The report also includes two pilot studies on registering as an individual microbusiness owner (Microempreendedor Individual, MEI) and paying taxes. under the simples nacional tax regime in five locations in Brazil. The study’s objectives are to provide a broader understanding of Brazil’s business regulatory environment and highlight good practices that can inspire improvements around the country. This report presents data current as of September 1, 2020 and includes comparisons with other economies.